2000
DOI: 10.2190/8g4w-2w33-ukub-0lh5
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Learning-Driven Constructs on Perceived Skill Development When Using Multimedia Instructional Materials

Abstract: Researchers disagree on the impact of multimedia on perceived skill development. This research investigated whether intervening variables such as task-technology factors might explain the difference in the research findings. An experiment was conducted where thirty-nine students worked on a case study using both paper-based and multimedia-based technologies. An exploratory factor analysis design employing a structural equation model was utilized to analyze the data. The findings from this study suggest a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Mbarika et al 21 confirmed that learners had a stronger sense of efficacy and perceived skill development when using multimedia versus paper-based tasks. These attributes are due to the learning-driven constructs within the technology which can be described as challenging, interesting, reflective, and interactive while learning with others.…”
Section: Implictions For Practice: Strengths and Weaknessesmentioning
confidence: 97%
“…Mbarika et al 21 confirmed that learners had a stronger sense of efficacy and perceived skill development when using multimedia versus paper-based tasks. These attributes are due to the learning-driven constructs within the technology which can be described as challenging, interesting, reflective, and interactive while learning with others.…”
Section: Implictions For Practice: Strengths and Weaknessesmentioning
confidence: 97%
“…Some suggested that video can enhance learning outcomes due to vivid and fascinating presentations; e.g., Nugent [35] compared several components of video presentations and generally found better retention for stories presented via the combination of visual and auditory information than those presented via a single information source. On the other hand, other studies reported little impact of video on learning outcome [14,30]. However, those studies did not use online video.…”
Section: Development Of Hypothesesmentioning
confidence: 98%
“…These two factors explain 60.768% of the total variance. Because it is common in social science research for a solution to be considered satisfactory if it accounts for around 60% of the total variance (Mbarika et al, 2000), we argue that determining two factors is acceptable.…”
Section: Resultsmentioning
confidence: 97%